MICROALGA E NIACINA COMO BIOINSUMO PARA PRODUÇÃO DE MUDAS DE MANJERICÃO EM SISTEMA HIDROPÔNICO - FETTE, Isabella Alves; SALLES, Josiane Souza; BINOTTI, Flávio Ferreira da Silva; SALLES, Jussara Souza; OLIVEIRA, Alessa Barbosa; FREITAS, Yasmin Karolaine Leal (ANAIS DO ENIC, 2025)
-